Reading Hume's Dialogues : a veneration for true religion - Sessions, William Lad (Indiana series in the philosophy of religion., 2002)
" ... Establishes the literary and philosophical greatness of the Dialogues in ways that even its warmest admirers have been unable to do before."--Terence PenelhumIn this lively reading of David Hume's Dialogues concerning Natural Religion, William Lad Sessions reveals a complex internal hermeneutic that gives new form, structure, and meaning to the work. Linking situations, character, style, and action to the philosophical concepts presented, Sessions finds meaning contained in the work itself and call